2016
DOI: 10.1016/j.joco.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of ophthalmology residents in the United States about residency programs and competency in relation to the International Council of Ophthalmology guidelines

Abstract: PurposeTo evaluate the perspective of ophthalmology residents in the US about their residency programs and compare the competency of residency programs to international competency levels set by the International Council of Ophthalmology (ICO).MethodsA cross-sectional web-based survey extracted from the ICO published competency standards was sent to program directors of ophthalmology residency programs in the US to forward it to current PGY-3, 4 residents, and residency graduates from 2011 to 2014.ResultsEighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
1
13
3
Order By: Relevance
“…For example, the overall satisfaction among ophthalmology residents was 34% in Jordan 3 and 36% in Iran. 6 However, the overall satisfaction in the current study is low compared with well-recognized international training programs in the United States 7 (93%) and Canada 4 (85%).…”
Section: Discussioncontrasting
confidence: 66%
“…For example, the overall satisfaction among ophthalmology residents was 34% in Jordan 3 and 36% in Iran. 6 However, the overall satisfaction in the current study is low compared with well-recognized international training programs in the United States 7 (93%) and Canada 4 (85%).…”
Section: Discussioncontrasting
confidence: 66%
“…Great efforts have been made to develop regional standards of ophthalmic training, develop standardized curricula and post-graduate fellowship or board level-exams. This is less than a recent survey of residents in the USA which reported a 94% ‘highly satisfied’ rating 8 .…”
Section: Discussionmentioning
confidence: 58%
“…A number of ophthalmology trainee surveys have been conducted over the past ten years, including Nigeria 7 , the USA 8, 9 , Canada 10 , Jordan 11 , India 12 , and China 13 , but no international survey of the training programs in Eastern, Central, and Southern Africa has been published to understand the current training provision and experience as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies conducted in North America,13,14,15,16,17 revealed that the residents were generally satisfied with didactic teaching, research activities and mentor-resident relationships because these activities were well delineated across the various residency programs according to the guidelines of the Accreditation Council for Graduate Medical Education. 18…”
Section: Discussionmentioning
confidence: 94%